Neuropsychological abnormalities in patients diagnosed with post-traumatic stress disorder (2017)
Posttraumatic Stress Disorder (PTSD) is presented as a dissociative identity clinical picture, accompanied by emotional disturbances such as depression, anxiety and apathy that lead to quality of life deterioration.